Mineralogy and Ore Characteristics of the Kujang Pb-Zn Skarn Deposit, Sukabumi Regency, West Java - Suryawan, Eka Harris; Idrus, Arifudin; Suyanto, Imam; Ilmawan, Ilham; Faruqi, M.Dzulfikar (Geological Engineering Department Universitas Gadjah Mada, 2023)
The Kujang Pb-Zn skarn deposit is known to be the newest skarn deposit found in the Sunda-Banda magmatic arc. The skarn orebodies are mostly hosted by limestone which might be the part of the Jampang Formation where dacite porphyry is interpreted to be the ore causative intrusion. Orebodies are mostly found at the contact between marbleized limestone and volcanic rocks and are controlled by NW-SE-trending strike-slip faults. Previous research on the mineralogy and ore characteristics of the Kujang Prospect remains limited on the preliminary studies. Using fieldwork data, petrography, ore microscopy, and assay data from core samples, this study is aimed to characterize the mineralogy of both alteration and ore of the deposit. The alteration of the Kujang Prospect skarn can be divided into 2 phases of alteration i.e. prograde and retrograde. The prograde alteration is characterized by the occurrence of clinopyroxene, wollastonite, and vesuvianite. Garnet is present in very rare amounts. the retrograde alteration is typified by epidote, chlorite, calcite and actinolite. Metalliferous minerals are represented by sphalerite, galena, pyrrhotite, chalcopyrite and pyrite. All ore minerals are formed at the early retrograde stage. the deposit’s average grade is 2.06% Pb, 6.45% Zn and 1.81% Cu.